Implementasi Kebijakan Pengelolaan Sampah Melalui Program Bank Sampah Di Kecamatan Kelapa Gading Kota Administrasi Jakarta Utara - Wahyudin, Ihsan; Susetyo, Ivan Budi (Jurnal Ilmu Administrasi Publik, 2024)
Residents in Kelapa Gading District, North Jakarta, face the problem of landfills because the daily volume of waste in DKI Jakarta continues to increase. In response, the government enacted Law number 18 of 2008 and Gubernatorial Regulation number 77 of 2020 concerning waste management. This research aims to analyze and evaluate the implementation of waste management policies through the waste bank program in the region. This research uses a descriptive method based on a qualitative approach with data collection techniques including observation, interviews and documentation. The informants consisted of 4 people, including the head of the Environmental Service, Chairman and members of the waste bank in Kelapa Gading District, as well as a public administration lecturer. The research results show that the implementation of the Waste Management Policy through the Waste Bank Program in Kelapa Gading District is in accordance with the regulations of Gubernatorial Regulation 77 of 2020 concerning Rukun Warga Waste Management and fulfills 4 research aspects, namely communication, resources, disposition and organizational structure. However, there are still obstacles in the communication and resource aspects that need to be improved to achieve optimal implementation. Barriers to implementing the policy include a lack of understanding of the policy, difficulties in socializing the program, limited infrastructure and adequate facilities, as well as the need to increase public awareness and face challenges in monitoring and changing policies. To overcome obstacles in implementing waste management policies through the waste bank program in Kelapa Gading District, efforts need to be made such as increasing inclusive socialization, establishing positive examples through pilot waste banks, strengthening supporting infrastructure, and carrying out good coordination and supervision.